Enhancing Student Higher Order Thinking Skills through Problem-Based Learning Media Integration - Al Farisi, Fadli Robby; Yulianti, Evy; HR, Nida Husna; Hidayah, Fajarotul; Hidayat, Dinnisa Haura Zhafira (FKIP Universitas Lampung, 2023)
Enhancing Student Higher Order Thinking Skills through Problem-Based Learning Media Integration. Objectives: This quantitative research employed a quasi-experimental nonequivalent control group design to investigate the impact of Problem-Based Learning (PBL) media on student higher order thinking skills (HOTS). Methods: The research was conducted with students from XI IPA 3 and XI IPA 4 classes at a high school. Findings: Students using PBL-based media exhibited a mean score of 83 for HOTS, with a notable n-gain of 0.7, categorized as high. In contrast, the control group achieved an average posttest score of 74.1, accompanied by an n-gain of 0.5, classified as medium. Statistical analysis indicated a t-value of 4.376, signifying a significant effect of PBL media on students’ HOTS. Implementing the PBL-based media in the learning process was highly successful, achieving an average implementation percentage of 100% with excellent criteria. Conclusion: These findings affirm the positive influence of PBL-based media on students’ HOTS,underlining its potential as an effective teaching strategy.Keywords: higher order thingking, learning media, problem-based learning.DOI: http://dx.doi.org/10.23960/jpp.v13.i3.202317